The Evidentiary Power of The Waqf Pledge Deed As Proof of Land Ownership : A Systematic Literature Review - Nu'tiha, Soaliha; Iksan; Aman Ma’arij (Journal of Transcendental Law, 2024)
The waqf pledge deed is a crucial legal document in Islamic law that provides the dedication of property to religious, charitable, or community purposes. This study used the systematic literature review (SLR) approach to gather, evaluate, and synthesize pertinent information about the evidential power of the waqf pledge deed as proof of land ownership. The empirical data is then evaluated using a normative legal method that includes both a statutory (statue approach) and a conceptual (conceptual approach).The study's findings indicate that research on waqf is expanding, with an emphasis on Islamic financial innovation, socioeconomic benefits, and digital technology integration. Cash waqf in Indonesia is critical to the development of the Islamic economy. To boost the effectiveness of waqf management, researchers are looking into integrating Islamic charitable tools with digitalization institutions. This expansion highlights the significance of waqf in economic empowerment and social development, with opportunities for further research in digital innovation and policy.